Understanding fair play basketball club players in perbasi jombang - Arnaz Anggoro Saputro; Ossa Viantina (Universitas Sebelas Maret, 2022)
Basketball is a sport in which body contact occurs between players, which often causes chaos during matches so that it can become a source of commotion that can injure the spirit of sportsmanship in sport (fair play). This research is a population study, so the entire population is used as a research sample, namely all basketball clubs sheltered by Perbasi Jombang, totaling 102 players. The research variable is the single variable, namely the understanding of fair play of basketball club players in Perbasi Jombang. The data collection method used a questionnaire technique, the data were analyzed using descriptive percentage analysis. Based on the results of the study, it is known that as many as 13 respondents (12.75%) have a very good level of understanding of fair play, 79 respondents (77.45%) have a good level of understanding of fair play and as many as 10 respondents (9.80%) have a good level of understanding of fair play. fairly good understanding of fair play. That understanding includes the meaning of the word fair play which is actually 82.23%, understanding the purpose of fair play by 77.78%, understanding the moral values contained in fair play by 83.74%, understanding the rules or fair play exponents. in basketball games by 72.84%, and the form of self-esteem reflected in fair play by 79.36%. It can be concluded that most of the basketball club players in Perbasi Jombang are good at understanding fair play in a basketball game